Recreational opportunities offered in Protected Natural Areas: analysis of the most visited National Parks in Brazil and the United States of America in 2017 - Gomes, Carolina Ribeiro; Figueiredo, Mucio do Amaral; Salvio, Geraldo Majela Moraes (Sociedade & Natureza, 2021)
National Parks (NPs) are instruments for nature protection and tourism that demand tools for proper visitation. With the advance of tourism in these areas, NPs assume a double responsibility: to maintain visitor experience quality and to contribute with all their potential to society. In this sense, the Recreation Opportunity Spectrum (ROS) tool categorizes “Visitation Opportunities” classes (Pristine, Primitive, Natural, Rural, and Urban) to identify specific attributes of each environment and each visiting public and, thus, organize tourist use. In this scenario, we aimed to analyze the opportunities offered in 10 National Parks, five in Brazil and five in the United States (US), to understand how different Opportunity Classes can influence tourist visitation. The data were drawn from bibliographic and documentary research. After identifying the tourist potential of each NP, we applied the ROS methodology. The results showed a relationship between the number of opportunities offered and the number of visitors received by the National Parks, confirming the assumption that, both in Brazilian and American parks, different recreational opportunities are related to the largest number of visitors. Thus, the Recreation Opportunity Spectrum (ROS) tool presents itself as an important management tool for tourism visitation. The possibility of creating visitation classes in natural areas must be widely used to guarantee sustainable tourism.